Aging exaggerates acute‐on‐chronic alcohol‐induced liver injury in mice and humans by inhibiting neutrophilic sirtuin 1‐C/EBPα‐miRNA‐223 axis. Issue 3 (5th December 2021) - Ren, Ruixue; He, Yong; Ding, Dong; Cui, Aoyuan; Bao, Huarui; Ma, Jing; Hou, Xin; Li, Yu; Feng, Dechun; Li, Xiaoling; Liangpunsakul, Suthat; Gao, Bin; et al.
Abstract: Background and Aims: Aging exacerbates liver neutrophil infiltration and alcohol‐associated liver disease (ALD) in mice and humans, but the underlying mechanisms remain obscure. This study aimed to examine the effect of aging and alcohol consumption on neutrophilic Sirtuin 1 (SIRT1) and microRNA‐223 (miR‐223), and their contribution to ALD pathogeneses. Approach and Results: Young and aged myeloid‐specific Sirt1 knockout mice were subjected to chronic‐plus‐binge ethanol feeding. Blood samples from healthy controls and patients with chronic alcohol drinking who presented with acute intoxication were analyzed. Neutrophilic Sirt1 and miR‐223 expression were down‐regulated in aged mice compared with young mice. Deletion of the Sirt1 gene in myeloid cells including neutrophils exacerbated chronic‐plus‐binge ethanol‐induced liver injury and inflammation and down‐regulated neutrophilic miR‐223 expression. Immunoprecipitation experiments revealed that SIRT1 promoted C/EBPα deacetylation by directly interacting with C/EBPα, a key transcription factor that controls miR‐223 biogenesis, and subsequently elevated miR‐223 expression in neutrophils. Importantly, down‐regulation of SIRT1 and miR‐223 expression was also observed in circulating neutrophils from middle‐aged and elderly subjects compared with those from young individuals. Chronic alcohol users with acute intoxication had a reduction in neutrophilic SIRT1 expression in young and middle‐aged patients, with a greater reduction in the latter group. The neutrophilic SIRT1 expression correlated with neutrophilic miR‐223 and serum alanine transaminase levels in those patients. Conclusions: Aging increases the susceptibility of alcohol‐induced liver injury in mice and humans through the down‐regulation of the neutrophilic SIRT1‐C/EBPα‐miR‐223 axis, which could be a therapeutic target for the prevention and/or treatment of ALD.